Penilaian Kinerja Keuangan Pada Koperasi Serba Usaha KPRI Karya Bhakti Palu - Nanang Qosim; Najrah T; Akhmad Akhmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to find out the condition of kpribi liquidity ratio of Karya Bhakti in 2010 - 2014, to know the condition of kpri rentability ratio of Karya Bhakti in 2010 - 2014, to know the condition of activity ratio in 2010 - 2014. The results showed kpri Karya Bhakti especially in 2010 slightly lower than in 2011, 2012 and 2013 increased, while in 2014 decreased compared to the previous year. Kpri Karya Bhakti's rentability is in a condition that tends to increase. The increase in SHU and the capital itself has changed so that the ratio condition also tends to increase. This shows the ability of KPRI Karya Bhakti in managing the rest of its business results. The rentability of Kpri by Bhakti increased from 2010 to 2012, while in 2013 to 2014 it decreased.The results showed that Kpri Karya Bhakti's activity is in a condition that tends to increase. The increase in sales and total assets has changed so that the ratio condition tends to increase. From 2010 to 2012 it increased. And in 2013 it declined, but in 2014 again increased.